The diversity of students' emotional intelligence and its influence on student activities in the learning process - Ninies Eryadini (PPPM STKIP PGRI Lamongan, 2021)
Intellectual intelligence (IQ) and emotional intelligence (EQ) are indispensable in the learning process. The two intelligences complement each other. The balance between intellectual intelligence and emotional intelligence is the key to successful learning for students. There are many potential students that can be developed. Various emotional intelligences in learning affect learning activities. Each student has a different emotional intelligence background, how to respond to the incoming stimulus is also different. The process of interaction during the learning process in the classroom is strongly influenced by emotional intelligence and social skills so it is necessary to consider the background of emotional intelligence in accompanying them during the learning process in the classroom. Students with high emotional intelligence are easier to interact, adapt to their learning environment. Emotional intelligence can be developed by providing a lot of experience to them directly to improve their emotional intelligence under the guidance of the teacher in the learning process.